Pola Komunikasi Kelompok dalam Membentuk Konsep Diri pada Komunitas Punk Taring Babi - Leasfita, Ade (Jurnal Mahardika Adiwidia, 2024)
The punk community is still a social phenomenon that is one of the focuses of public attention because of their appearance and the things they do. Most of the people still consider them negative. The purpose of this study was to understand and know the communication patterns of the Taring Babi Punk Community in shaping the Self-Concept through the activities carried out by them. This research is a discussion to describe a reality in social phenomena that occur in society. The method used in this research is descriptive qualitative method, namely by making observations and direct interviews with informants. For the data processing technique itself, it uses data reduction techniques, data presentation and also draws conclusions. For the validity of the data using source triangulation technique. The results of this study indicate that the Taring Babi Punk Community uses communication patterns as part of their communication process to the community. This communication pattern forms a positive self-concept for the Taring Babi Punk Community. This research also reveals how the Taring Babi Punk Community forms their self-concept through the process of social interaction and also the social actions they take to be accepted by the community.Kata kunci: Communication, Self-Concept, Punk Community